Modes of Brassinosteroid Activity in Cold Stress Tolerance - Ramirez, Veronica E.; Poppenberger, Brigitte (Frontiers in Plant Science, 2020)
Cold stress is a significant environmental factor that negatively affects plant growth and development in particular when it occurs during the growth phase. Plants have evolved means to protect themselves from damage caused by chilling or freezing temperatures and some plant species, in particular those from temperate geographical zones, can increase their basal level of freezing tolerance in a process termed cold acclimation. Cold acclimation improves plant survival, but also represses growth, since it inhibits activity of the growth-promoting hormones gibberellins (GAs). In addition to GAs, the steroid hormones brassinosteroids (BRs) also take part in growth promotion and cold stress signaling; however, in contrast to Gas, BRs can improve cold stress tolerance with fewer trade-offs in terms of growth and yields. Here we summarize our current understanding of the roles of BRs in cold stress responses with a focus on freezing tolerance and cold acclimation pathways.